Fat mass vs body mass index in anticipation of aerobic capacity to monitor weight gain in sports women - Zerf, Mohammed; Saci, Mohammed; Mokkedes, Moulay Idris; Kohli, Kamel; Houar, Abdelatif; Bengoua, Ali (https://r.search.yahoo.com/_ylt=AwrEeNsTMD5cKzMAzQQPxQt.;_ylu=X3oDMTByOHZyb21tBGNvbG8DYmYxBHBvcwMxBHZ0aWQDBHNlYwNzcg--/RV=2/RE=1547608212/RO=10/RU=https%3a%2f%2fmedcraveonline.com%2fMOJWH%2fMOJWH-08-00204.pdf/RK=2/RS=EDepkcpDBExKTAeP2bRD_zuOBkM-, 2019)
The objective of the current study is built in body fat as a predictor of ideal weight to promote health and fitness body weight. To test this hypothesis, we founded on the relationship between fat mass index vs index body mass composition to improve aerobic capacity as control of body weight. For the proposition, 60 women sports under 22. We’re controlled by the cooper test as physiological parameter estimated VO2 max and the weight and height to estimate BMI and body fat as anthropometric measurements. Based on our database and analyses, we confirm the hypothesis, which argued that BMI alone should not be used to determine an “ideal” body weight. Since the level of VO2 max is the best predictor of aerobic capacity and adjusted fitness body weight based on the ratio of body fat among sportswomen. However, to develop an equation more studies are required to prove this hypothesis.
Keywords: ody, fat, BMI, aerobic, capacity, weight, gain, sports, womenMOJ Women’s Health Research ArticleOpen Access